Business Results and Well-Being: An Engaging Leadership Intervention Study - van Tuin, Lars (Int J Environ Res Public Health, 2020)
The present quasi-experimental study tested the business impact of a leadership development program focusing on psychological well-being through the satisfaction of basic psychological needs. Based on the concept of engaging leadership and self-determination theory, the 8-month program targeted midlevel team leaders of the customer fulfilment center of a health systems multinational organization. The program was designed in co-creation between senior leadership and the team leaders that participated in the program. Outcomes showed positive business results through significant increases in a preselected key performance indicator and decreased employee absenteeism. Through changes in autonomy satisfaction and intrinsic motivation, the team leaders (N = 14) benefitted in a moderate to very large extent relative to a similar control group (N = 52). In contrast, team members (N = 148) displayed no such benefits. Specifically, higher levels of autonomy satisfaction are said to lead to higher levels of psychological well-being and motivation. Still, the link with business performance is absent in most organizational studies within self-determination theory, making the present study one of the first to fill this gap. The study discloses the program design, compares the effects to a relevant control group, evaluates the lessons learned, and provides practical suggestions.